National survey and analysis of barriers to the utilisation of the 2005 Mental Capacity Act by people with bipolar disorder in England and Wales - Morriss, Richard; Mudigonda, Mohan; Bartlett, Peter; Chopra, Arun; Jones, Steven (Taylor & Francis, 2017)
Background: The Mental Capacity Act (2005) (MCA) provides a legal framework for advance planning for both health and welfare in England and Wales for people if they lose mental capacity e.g. through mania or severe depression. Aims: To determine the proportion of people with bipolar disorder (BD) who utilise advance planning, their experience of using it and barriers to its implementation. Methods: National survey of people with clinical diagnosis of BD of their knowledge, use and experience of the MCA. Thematically analysed qualitative interviews with maximum variance sample of people with BD. Results: 544 respondents with BD participated in the survey; 18 in the qualitative study. 403 (74.1%) believed making plans about their personal welfare if they lost capacity to be very important. 199 (36.6%) participants knew about the MCA. 54 (10%), 62 (11%) and 21 (4%) participants made advanced decisions to refuse treatment, advance statements and lasting power of attorney respectively. Barriers included not understanding its different forms, unrealistic expectations and advance plans ignored by services. Conclusion: In BD the demand for advance plans about welfare with loss of capacity was high but utilisation of the MCA was low with barriers at service user, clinician and organisation levels.